2008
DOI: 10.1007/s00105-007-1465-z
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition in patients with leg ulcers

Abstract: Chronic wounds occur in 1-2% of the population. After the age of 80 the incidence raises up to 4-5%. Leg ulcers are the most frequent diagnosed chronic wound. In this most often affected age group malnutrition develops more frequently compared to the total population. The combined presence of chronic wounds and malnutrition suggests a potential causative connection. In this clinical investigation, data evaluating the nutritional status in patients with chronic leg ulcers, derived from clinical examination, med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
(26 reference statements)
0
3
0
1
Order By: Relevance
“…Vedno ve je dokazov, da se zaradi pomanjkanja hranil poslabša celjenje rane. Stanje prehranjenosti oseb z nezaceljeno golenjo razjedo je bistveno slabše kot pri tistih, ki so imeli golenjo razjedo že zaceljeno (Dealey, 2005;Graue et al, 2008). Pri ljudeh, ki so dobro hranjeni, je as bivanja v bolnišnici krajši, incidenca zapletov je nižja, celjenje ran pa je boljše (Banks et al, 2013;Stechmiller, 2010).…”
Section: Vpliv Prehrane Na Celjenje Ranunclassified
“…Vedno ve je dokazov, da se zaradi pomanjkanja hranil poslabša celjenje rane. Stanje prehranjenosti oseb z nezaceljeno golenjo razjedo je bistveno slabše kot pri tistih, ki so imeli golenjo razjedo že zaceljeno (Dealey, 2005;Graue et al, 2008). Pri ljudeh, ki so dobro hranjeni, je as bivanja v bolnišnici krajši, incidenca zapletov je nižja, celjenje ran pa je boljše (Banks et al, 2013;Stechmiller, 2010).…”
Section: Vpliv Prehrane Na Celjenje Ranunclassified
“…Malnutrition develops more often in the elderly than in the general population. The coexistence of chronic wounds and malnutrition suggests a potential causal relationship [ 1 ]. There is an increased risk of chronic wounds with age.…”
Section: Introductionmentioning
confidence: 99%
“…Available data underline the importance and necessity of using the recommended screening methods. It has been shown that the measurement of body weight or waist-to-hip ratio alone is not sufficient to assess the nutritional status of patients with wounds [ 1 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…[4] The label chronic or delayed was applied to wounds in which compromised healing was anticipated, usually because of complex underlying pathologies such as diabetes mellitus, vascular disease, malignancy, malnutrition, or morbid obesity. [5][6][7][8] Other factors which adversely affected wound healing included drug use, hypoxia, the presence of another wound, nutritional problems and tissue necrosis. Diabetes delays wound healing by diminishing sensation and arterial inflow; protein calorie malnutrition and deficiencies of vitamin A, C and zinc also impair the normal wound healing mechanism.…”
Section: Introductionmentioning
confidence: 99%